2020
DOI: 10.1038/s41467-020-16495-z
|View full text |Cite
|
Sign up to set email alerts
|

Weaker neural suppression in autism

Abstract: Abnormal sensory processing has been observed in autism, including superior visual motion discrimination, but the neural basis for these sensory changes remains unknown. Leveraging well-characterized suppressive neural circuits in the visual system, we used behavioral and fMRI tasks to demonstrate a significant reduction in neural suppression in young adults with autism spectrum disorder (ASD) compared to neurotypical controls. MR spectroscopy measurements revealed no group differences in neurotransmitter sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 84 publications
4
23
0
Order By: Relevance
“…Contrary to prior research that has demonstrated associations between GABA levels and sensory processing in ASD [ 33 35 ], no associations were found between GABA+ values in any VOI and sensory processing symptoms across all participants or within TD or ASD groups. Nevertheless, our results are consistent with a recent study that found no association between GABA+ concentrations and behavioral and fMRI measures of visual spatial suppression [ 67 ]. Rather, we observed significant correlations between rTPJ Glx levels and all four sensory processing quadrants across both groups, which was primarily the result of associations within the ASD group, for Sensitivity and Avoidance subscales; greater scores on these subscales, indicative of increased hypersensitivity to sensory input, were associated with atypically decreased Glx levels in the ASD group, suggesting that reduced glutamate may contribute to sensory processing impairments in ASD.…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to prior research that has demonstrated associations between GABA levels and sensory processing in ASD [ 33 35 ], no associations were found between GABA+ values in any VOI and sensory processing symptoms across all participants or within TD or ASD groups. Nevertheless, our results are consistent with a recent study that found no association between GABA+ concentrations and behavioral and fMRI measures of visual spatial suppression [ 67 ]. Rather, we observed significant correlations between rTPJ Glx levels and all four sensory processing quadrants across both groups, which was primarily the result of associations within the ASD group, for Sensitivity and Avoidance subscales; greater scores on these subscales, indicative of increased hypersensitivity to sensory input, were associated with atypically decreased Glx levels in the ASD group, suggesting that reduced glutamate may contribute to sensory processing impairments in ASD.…”
Section: Discussionsupporting
confidence: 93%
“…Experiments examining how it modulates visual performance and neuronal activity in visual cortex have found disparate attentional effects on stimulus-evoked neural responses, such as the contrast-response function attention field is small. Remarkably, previous psychophysical (Herrmann et al, 2010;Schallmo et al, 2020;Schwedhelm et al, 2016;Zhang et al, 2016), electroencephalography (Itthipuripat et al, 2014(Itthipuripat et al, , 2019, and voxel-based functional magnetic resonance imaging (Hara et al, 2014) studies have reported that the patterns of behavioral performance, steady-state visual evoked potentials, and voxel-averaged neurometric functions, respectively, are all consistent with the predictions of normalization model of attention. However, little is known regarding whether visual bottom-up attention with and without awareness is governed by this common neural computation: normalization and how awareness could modulate the gain changes induced by attentional selection.…”
Section: Introductionsupporting
confidence: 68%
“…In addition, the macromolecular contamination of GABA acquired using the MEGA-PRESS sequence could have a major impact on the correlation with behaviour (Mikkelsen et al 2018a). A recent study using a large sample size (N = 62) also showed no correlation between surround suppression and GABA+ (Schallmo et al 2020). This lends further support to the view that the involvement of cortical inhibition in spatial context effects is likely to be more complex than previously thought.…”
Section: Cortical Inhibition and Spatial Context Modulationmentioning
confidence: 58%
“…Together, these have presented mixed evidence supporting a role of neurochemistry in surround suppression. While some studies reported a link between GABA+ and orientation (Yoon et al 2010), contrast (Cook et al 2016) and motion-specific (Pitchaimuthu et al 2017) surround suppression, two recent studies have not supported a relationship (Schallmo et al 2018(Schallmo et al , 2020. Schallmo et al (2018) applied multiple complementary methods, including multimodal neuroimaging, computational modelling, and pharmacology to evaluate whether higher GABA+ led to stronger surround suppression.…”
Section: Cortical Inhibition and Spatial Context Modulationmentioning
confidence: 99%